Pengaruh Investment Opportunity Set, Sustainability Reporting dan Corporate Governance terhadap Nilai Perusahaan pada Perusahaan Manuaktur yang Terdaftar di Bursa Efek Indonesia (BEI) - Erawati, Teguh; Handayani, Lia (Universitas Hamzanwadi, 2024)
The purpose of this study is to describe the effect of investment opportunity set and sustainability reporting on firm value with corporate governance as a moderation variable. This research model is quantified by the population of this study as a manufacturing company listed on the Indonesia Stock Exchange 2019-2022. Samples were purposively determined, totaling 116 manufacturing companies. Data is secondary, data is taken from www.idx.co.id . Data analysis uses multiple regression analysis, autocorrelation, F test, R² test and t test. The research results include 1) ) investment opportunity sets have a positive effect on firm value, 2) sustainability reporting has a positive effect on firm value, 3) corporate governance that proxies managerial ownership has a positive effect on firm value